2003
DOI: 10.2134/agronj2003.1566
|View full text |Cite
|
Sign up to set email alerts
|

Drought Avoidance Assessment for Summer Annual Crops Using Long‐Term Weather Data

Abstract: during the cropping season when water supply is likely to be more abundant. This approach has been an effec-Seasonal rainfall is a key factor determining yield of nonirrigated, tive tool for crops grown in monsoonal climates where summer crops. In temperate regions, however, systematic analyses of they are sown near the beginning of the wet season and long-term weather data have not been used for directing breeding programs or for crop management options. We evaluated long-term mature before the dry season (Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…In line with the results from some previous studies [26,28,36,67,75,76], it was found that the atmospheric conditions over NEB influences the upper soil water balance dynamic. This characteristic is reflected by a moderate coupling strength between the AWD and SWDIS from June 2010 to December 2013 in the entire NEB (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with the results from some previous studies [26,28,36,67,75,76], it was found that the atmospheric conditions over NEB influences the upper soil water balance dynamic. This characteristic is reflected by a moderate coupling strength between the AWD and SWDIS from June 2010 to December 2013 in the entire NEB (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 89%
“…The concept of the Atmospheric Water Deficit (AWD) was proposed by Purcell et al [28]. AWD is a suitable tool to identify the drought dynamics related to soil water storage [26,67].…”
Section: Atmospheric Water Deficit Derived From In Situ Observations mentioning
confidence: 99%
“…Vapor pressure defi cit was calculated for each corresponding ambient air temperature using methods described by Purcell et al (2003) and Allen et al (1998). First, CTD was analyzed using ANOVA, similar to the model discussed for conductance.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, weekly comparisons were made because one week is the time interval commonly used by farmers for irrigation schedules [15]. Therefore, weekly maps of the drought indices (SWDI Rawls , SWDI CYL , SMADI, SMDI and SWetDI) were estimated over the agricultural areas of the Castilla y León region.…”
Section: Comparison Strategymentioning
confidence: 99%
“…To improve this issue, a self-calibrating PDSI (sc-PDSI) was proposed [14]. The Atmospheric Water Deficit (AWD) is also a meteorological index that uses the simple water balance between evapotranspiration (ET) and precipitation [15,16]. passive and active microwave satellite sensors from 1978 to 2015 [43].…”
Section: Introductionmentioning
confidence: 99%